2005
DOI: 10.1542/peds.2004-1193
|View full text |Cite
|
Sign up to set email alerts
|

Medical Homes for At-Risk Children: Parental Reports of Clinician-Parent Relationships, Anticipatory Guidance, and Behavior Changes

Abstract: Among at-risk families, we found an association between parental ratings of the medical home and parental reports of the completeness of anticipatory guidance regarding selected injury and illness prevention topics. Parents' trust of the clinician was associated with parent-reported behavior changes for discussed topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Because of the current emphasis on patientcentered primary care, where discussions are tailored to the concerns and needs of the family, certain injuryprevention issues may be omitted if the family confidently asserts that their home is "infant proofed." 18 Recommending review of certain core "safety practices" at all visits will ensure families have needed injury-prevention information. Tailoring anticipatory guidance about injury prevention to specifically address the possible housing and safety issues prevalent in low-income, urban areas is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the current emphasis on patientcentered primary care, where discussions are tailored to the concerns and needs of the family, certain injuryprevention issues may be omitted if the family confidently asserts that their home is "infant proofed." 18 Recommending review of certain core "safety practices" at all visits will ensure families have needed injury-prevention information. Tailoring anticipatory guidance about injury prevention to specifically address the possible housing and safety issues prevalent in low-income, urban areas is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Research studies have shown that the perpetrator of CAN can be a victim of IPV (Casanueva et al, 2007;Coohey, 2004;Margolin, Gordis, Medina, & Oliver, 2003), a perpetrator of IPV (Lutenbacher, 2002;Shipman, Rossman, & West, 1999), or both (Dixon, Hamilton-Giachritsis, Browne, & Ostapuik, 2007). Other research studies have failed to state the identity of the perpetrator clearly (Kohla, Edleson, English, & Barth, 2005;Nelson et al, 2005). Reports in these studies are usually based on self-reports made by female victims to government agencies, the police, and social services organizations.…”
Section: Patterns Of Co-occurrencementioning
confidence: 99%
“…Although some studies have included all children, it was unclear if the positive associations found were due solely to the effect of CSHCN in the study populations, or if they exist independent of CSHCN. 12,[30][31][32][33][34][35][36][37][38][39][40][41] Our findings suggest that the benefits of the medical home for children without special health care needs mirror those experienced by CSHCN.…”
Section: Discussionmentioning
confidence: 89%